The Influence of Competence and Work Motivation on Employee Performance at the Health Sub-department of the City of South Jakarta Administration - Riptono; Yusuf Saptedja (IJESS International Journal of Education and Social Science, 2021)
The public's need for better, friendlier, and higher quality health services is increasing. Seeing conditions like this, of course, hard work is needed in an effort to reduce the mortality rate, including improving the skills of health workers in handling children under five, especially midwives and nurses at the puskesmas as the front line of service providers. Thus, the South Jakarta City Administration of Health Sub-Department is required to be able to show quality performance that is in accordance with community expectations and in line with the development of medical science and technology. To be able to improve good performance and at the same time meet the demands of the community, each employee must have adequate capabilities in accordance with their respective fields of duty. In other words, every employee, both medical (doctors), paramedics (midwives/nurses) and administrative personnel must have. by employees or human resources who have competence. Paramedics (midwives/nurses) as well as administrative staff must have. Likewise, the health service provider agency (South Jakarta City Administration Health Sub-dept.), in providing health services to the community has been supported by competent employees or human resources.